Efektivitas Sterilisasi Kimiawi Eksplan Pucuk Artemisia annua Linn. dengan Berbagai Prosedur Sterilisasi Pada Tahap Inisiasi In Vitro - Ivan Tjahja Pranata; Maria Marina Herawati (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
In vitro culture is one of important method generally used for improving agronomic traits in Artemisia annua such as enhancing artemisinin. However, the method has main inhibitor factor which often involved in early micropropagation stage, that is contamination. This research aimed to find the most effective sterilization procedure for diminishing the contamination rate of Artemisia annua shoot explant, without causing high mortality rate.sterilization procedure treatment in this research used 8 type of sterilant i.e. etanol, HgCl2, Bayclin®, Mama Lime®, SOS®, Ligent®, Sunlight®, dan Carex®. This research used completely randomized design with 25 treatments. Each treatment replicated 3 times, each 20 bottle/replication. The observation comprised total contamination rate, bacteria contamination rate, mold contamination rate, and mortality rate. The research result showed that sterilization step with Carex® mixed with SOS® in 30 seconds which continue with HgCl2 in 7 minutes is the most optimal sterilization procedure to diminish the contaminant of shoot explant without enhance the mortality rate.